(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article researches some number ways of realizing the system of values in the contemporary novel from the perspective of the postmodern play with genre strategies and narratives. It describes those peculiarities and techniques with the help of which the system of values in the text is constructed.